Feeding a diet contaminated with ochratoxin A for chickens at the maximum level recommended by the EU for poultry feeds (0.1 mg/kg). 1. Effects on growth and slaughter performance, haematological and serum traits. Issue 1 (2nd May 2013) - Pozzo, L.; Salamano, G.; Mellia, E.; Gennero, M.S.; Doglione, L.; Cavallarin, L.; Tarantola, M.; Forneris, G.; Schiavone, A.
Summary: The European Commission Recommendation 2006/576/EC, suggests that the maximum level of Ochratoxin A (OTA) in poultry feeds should be set at 0.1 mg OTA/kg. Thirty‐six one‐day‐old male Hubburd broiler chickens were divided into two groups, a Control (basal diet) and an Ochratoxin A (basal diet + 0.1 mg OTA/kg) group. The growth and slaughter performance traits were recorded. The liver, spleen, bursa of Fabricius and thymus weights were measured. The erythrocyte and leukocyte numbers were assayed in blood samples, and the heterophils to lymphocytes (H/L) ratio was determined. Alpha‐1‐acid glycoprotein (AGP), lysozyme, the total protein and the electrophoretic pattern were evaluated in serum samples. Liver enzymes (alanino aminotransferase, ALT and aspartate aminotransferase, AST) and kidney function parameters (uric acid and creatinine) were quantified. The results revealed that feeding a 0.1 mg OTA/kg contaminated diet to chicks caused a decrease in the absolute thymus weight (p < 0.05) and a lower total protein (p < 0.01), albumin (p < 0.01), alpha (p < 0.05), beta (p = 0.001) and gamma (p = 0.001) globulins serum concentration in the Ochratoxin A group. Moreover, the albumin‐to‐globulin (A/G) ratio of the OTA‐treated animals resulted to be higher (p < 0.05). Feeding broiler chickens, a diet contaminated with the maximum level admitted by the European Commission Recommendation (0.1 mg OTA/kg), did not affect the animal performance, slaughter traits, organ weights, haematological parameters, liver enzyme or renal function parameters concentrations but had an overall immunosuppressant effect, with reduction in the thymus weight and of the total serum protein, albumin, alpha, beta and gamma globulins concentration.